2013
DOI: 10.1111/jzo.12044
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the parotoid macroglands in Phyllomedusa leaf frogs

Abstract: The parotoid macroglands of toads (bufonids) and leaf frogs (hylids) are used in passive defence against predators. The parotoids release poison when the amphibian is bitten by a predator. Despite the apparent similarity, the anatomical and histological structure of these macroglands in hylids is poorly studied when compared with those of bufonids. In this paper, we focused on the morphology of the macroglands of P. distincta, a leaf frog endemic to the Brazilian Atlantic rainforest, comparing their structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 26 publications
1
35
0
2
Order By: Relevance
“…As the basal bufonid Rhaebo guttatus also presents a complex parotoid macrogland composed of highly packed glands (Jared et al, ; Mailho‐Fontana et al, ), parotoids in bufonids seem to be a specialized macrogland different from parotoids of other groups. For instance, parotoids of hylids do not share the same complex arrangement as those of bufonids, and their secretion products are of a different chemical nature (Antoniazzi et al, ). Another example of a macrogland consisting of a complex arrangement of glands is the femoral gland of some mantelline frogs, which consists of circularly arranged granular glands that secrete their products into a central external depression (Vences et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the basal bufonid Rhaebo guttatus also presents a complex parotoid macrogland composed of highly packed glands (Jared et al, ; Mailho‐Fontana et al, ), parotoids in bufonids seem to be a specialized macrogland different from parotoids of other groups. For instance, parotoids of hylids do not share the same complex arrangement as those of bufonids, and their secretion products are of a different chemical nature (Antoniazzi et al, ). Another example of a macrogland consisting of a complex arrangement of glands is the femoral gland of some mantelline frogs, which consists of circularly arranged granular glands that secrete their products into a central external depression (Vences et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study of the ontogeny of the postorbital/supratympanic region showed that these diverse types of glands differentiate from similar syncytial glands, suggesting that the differentiation of the glands occurs during postmetamorphic development. A particular characteristic of the parotoid gland of bufonids is the presence of differentiated mucous glands around the duct of the large glands (Jared et al, ; Antoniazzi et al, ); in R. arenarum , these mucous glands were only observed around the duct of the central glands. Glands surrounding the ducts differ from the other mucous glands of the body, both in their function and their morphological characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occurrence of three serous gland types is unusual in anuran skin, where no more than two different types were previously reported. Actually, three syncytial gland types have been also described in leaf frogs of the genus Phyllomedusa (Delfino et al, ; Nosi et al, ), but this variety includes secretory units specialized in producing skin wax (Blaylock et al, ; Antoniazzi et al, ) that therefore represent a serous‐derived rather than a proper serous type (Delfino et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is the predator who causes its own poisoning, which can often be lethal (Sakate and Lucas de Oliveira, ; Jared and Antoniazzi, ; Jared et al, ). Predator's self‐poisoning is characteristic of amphibian defense, which is classified as a “passive defense” (Jared and Antoniazzi, ; Antoniazzi et al, ), as opposed to “active defense” presented, for example, by the snakes, who attack the aggressor and inject their venom through glands compressed by surrounding muscles (Kochva, ; Pough et al, ; Jared et al, ).…”
mentioning
confidence: 99%